From pre-service to in-service education in English teaching: what do teachers in Serra Talhada-PE report? (Olhar de Professor, 2024)
This article presents and discusses data collected for the scientific initiation project “The education of English teachers and its implications for the public schools in Serra Talhada”, developed from 2021 to 2022. The aim of the study was to collect in-service educational demands of city school English teachers working in Serra Talhada-PE based on their professional profiles. First, we identified schools that offer English language teaching in basic education. Then, we interviewed nine participant-teachers through a structured interview and analyzed their answers interpretatively in the light of the literature review. The interviews were firstly conducted online, due to the pandemic, but they turned to in-person modality afterwards. It was possible to verify their self-perceptions on fluency and their difficulties in articulating their knowledge about methods and teaching-learning practices.
Keywords: English teaching; Teacher education; City school system